Synergistic interactions between PBDEs and PCBs in human neuroblastoma cells. Issue 4 (20th March 2012) - Pellacani, C.; Tagliaferri, S.; Caglieri, A.; Goldoni, M.; Giordano, G.; Mutti, A.; Costa, L. G.
<x xml:space="preserve">Abstract</x> Polybrominated diphenyl ethers (PBDEs) and polychlorinated biphenyls (PCBs) are ubiquitous environmental pollutants. Exposure to these chemicals has been associated with developmental neurotoxicity, endocrine dysfunction, and reproductive disorders. Humans and wildlife are generally exposed to a mixture of these environmental pollutants, highlighting the need to evaluate the potential effects of combined exposures. In this study, we investigated the cytotoxic effects of the combined exposure to two PBDEs and two PCBs in a human neuronal cell line. 2, 2′, 4, 4′‐Tetrabromodiphenyl ether, 2, 2′, 4, 4′, 5‐pentabromodiphenyl ether, PCB‐126 (3, 3′, 4, 4′, 5‐pentachlorobiphenyl; a dioxin‐like PCB), and PCB‐153 (2, 2′, 4, 4′, 5, 5′‐hexachlorobiphenyl; a non‐dioxin‐like PCB) were chosen, because their concentrations are among the highest in human tissues and the environment. The results suggest that the nature of interactions is related to the PCB structure. Mixtures of PCB‐153 and both PBDEs had a prevalently synergistic effect. In contrast, mixtures of each PBDE congener with PCB‐126 showed additive effects at threshold concentrations, and synergistic effects at higher concentrations. These results emphasize the concept that the toxicity of xenobiotics may be affected by possible interactions, which may be of significance given the common coexposures to multiple contaminants. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 418–427, 2014.